Radiomics-Based Preoperative Prediction of Lymph Node Status Following Neoadjuvant Therapy in Locally Advanced Rectal Cancer - Zhou, Xuezhi; Yi, Yongju; Liu, Zhenyu; Zhou, Zhiyang; Lai, Bingjia; Sun, Kai; Li, Longfei; Huang, Liyu; Feng, Yanqiu; Cao, Wuteng; Tian, Jie (Frontiers in Oncology, 2020)
Background and purpose: Lymph node status is a key factor for the recommendation of organ preservation for patients with locally advanced rectal cancer (LARC) following neoadjuvant therapy, but is generally confirmed post-operation. This study aimed to preoperatively predict lymph node status following neoadjuvant therapy using multiparametric magnetic resonance imaging (MRI)-based radiomic signature. Materials and methods: A total of 391 patients with LARC who underwent neoadjuvant therapy and TME were included, of which 261 and 130 patients were allocated to the primary cohort and validation cohort, respectively. Tumor area, as determined by preoperative MRI, underwent radiomics analysis to build a radiomic signature related to lymph node status. Two radiologists reassessed lymph node status on MRI. The radiomic signature and restaging results were included in multivariate analysis to build a combined model for predicting lymph node status. Stratified analyses were performed to test the predictive ability of the combined model in patients with post-therapeutic MRI T1-2 or T3-4 tumors, respectively. Results: The combined model was built in the primary cohort, and predicted lymph node metastasis (LNM+) with an area under the curve of 0.818 and a negative predictive value (NPV) of 93·7% in the validation cohort. Stratified analyses indicated that the combined model could predict LNM+ with a NPV of 100% and 87·8% in the post-therapeutic MRI T1-2 and T3-4 subgroups, respectively. Conclusion: This study reveals the potential of radiomics as a predictor of lymph node status for patients with LARC following neoadjuvant therapy, especially for those with post-therapeutic MRI T1-2 tumors.